Positional information in axolotl and mouse limb extracellular matrix is mediated via heparan sulfate and fibroblast growth factor during limb regeneration in the axolotl (Ambystoma mexicanum) - Phan, Anne Q. (Regeneration (Oxf), 2015)
Urodele amphibians are unique among adult vertebrates in their ability to regenerate complex body structures after traumatic injury. In salamander regeneration, the cells maintain a memory of their original position and use this positional information to recreate the missing pattern. We used an in vivo gain‐of‐function assay to determine whether components of the extracellular matrix (ECM) have positional information required to induce formation of new limb pattern during regeneration. We discovered that salamander limb ECM has a position‐specific ability to either inhibit regeneration or induce de novo limb structure, and that this difference is dependent on heparan sulfates that are associated with differential expression of heparan sulfate sulfotransferases. We also discovered that an artificial ECM containing only heparan sulfate was sufficient to induce de novo limb pattern in salamander limb regeneration. Finally, ECM from mouse limbs is capable of inducing limb pattern in axolotl blastemas in a position‐specific, developmental‐stage‐specific, and heparan sulfate‐dependent manner. This study demonstrates a mechanism for positional information in regeneration and establishes a crucial functional link between salamander regeneration and mammals.